AN EVENT STUDY OF MARKET REACTION TO PRESIDENTIAL ELECTION ANNOUNCEMENTS IN INDONESIA - Fitratul Huda (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2025)
This study examines how presidential election announcements influence Indonesia’s financial markets, focusing on the Jakarta Composite Index (JCI). Using an event study methodology with data from the 2019 and 2024 election cycles, we analyze abnormal returns across key political announcements. The findings show that candidate introductions trigger the strongest positive market reactions, particularly in consumer goods and financial services, while infrastructure and mining exhibit weaker responses. Elevated volatility and trading volumes underscore heightened uncertainty, yet also highlight investor sensitivity to credible and transparent economic agendas. These results provide new evidence on the interaction between politics and markets in an emerging democracy, offering practical insights for investors in portfolio allocation and for policymakers seeking to maintain stability through clear communication.